2010
DOI: 10.1136/gut.2010.208595
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating indocyanin green clearance into the Model for End Stage Liver Disease (MELD-ICG) improves prognostic accuracy in intermediate to advanced cirrhosis

Abstract: ICG had the highest predictive value of the examined tests. Its incorporation into the MELD adds an estimation of liver blood flow and renders the new score MELD-ICG more accurate in predicting survival in intermediate to advanced cirrhosis than the MELD and MELD-Na.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 30 publications
2
57
1
1
Order By: Relevance
“…Moreover, other laboratory data, including the low platelet count, elevation of the fibrotic markers, slow ICG elimination and a delay in the GSA uptake, in the liver suggested that ascites in the present patient was induced by liver cirrhosis (12)(13)(14)(15). However, previous reports have demonstrated a discrepancy in the high TP level in the ascites if the ascites is caused by liver cirrhosis (4,10,16,17).…”
Section: Discussioncontrasting
confidence: 44%
“…Moreover, other laboratory data, including the low platelet count, elevation of the fibrotic markers, slow ICG elimination and a delay in the GSA uptake, in the liver suggested that ascites in the present patient was induced by liver cirrhosis (12)(13)(14)(15). However, previous reports have demonstrated a discrepancy in the high TP level in the ascites if the ascites is caused by liver cirrhosis (4,10,16,17).…”
Section: Discussioncontrasting
confidence: 44%
“…As above discussed, total liver blood flow and hepatic functional reserve are reflected by ICGR15, often used as a prognostic marker in decompensated cirrhotic patients and in candidates to resective liver surgery [50] . In cirrhotic patients admitted to resective surgery, preexisting PH and postoperative parenchymal dysfunction are among the most common causes of PHLF.…”
Section: Icgr15 In Ph: a Role As A Non Invasive Marker?mentioning
confidence: 99%
“…It is also important to decide the proper time for liver transplantation and to choose the appropriate candidates for hepatic partial resection. 1,23 Estimating the functional reserve of the remnant liver in patients with liver cirrhosis or severe steatosis is especially important to minimize the risk of postoperative liver failure. Traditionally, indocyanin green (ICG) clearance test and scintigraphy with technetium-99m ( 99m Tc) mebrofenin have been used for evaluating liver function.…”
Section: Clinical Applications Of Gadoxetate-enhanced Mri Evaluation mentioning
confidence: 99%